2021
DOI: 10.1590/2317-1782/20202020076
|View full text |Cite
|
Sign up to set email alerts
|

Protocolo de evaluación y valores de referencia de la ganancia del reflejo vestíbulo-ocular (RVO) en el plano horizontal registrado mediante el video-Head Impulse Test (v-HIT) en población pediátrica

Abstract: RESUMEN Objetivo Elaborar un protocolo de evaluación y establecer valores de referencia de las ganancias del reflejo vestíbulo-ocular del canal semicircular horizontal obtenidas con el v-HIT en población pediátrica sin alteraciones vestibulares. Método Estudio cuantitativo, analítico, no experimental con muestreo no probabilístico por conveniencia. Se seleccionaron 39 sujetos entre 5 a 17 años, los cuales cumplieron los criterios de inclusión y exclusión. Resultados El promedio de la ganancia obtenida para … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…More specifically, they found the most pronounced increase in VOR gain during early infancy until the age of 6 years old, after which a slower progression toward adultlike values was noted by the age of 16 years. The latter findings imply that progression in VOR gain mainly occurs early in life, which underlines the importance of age-appropriate normative data (Wiener-Vacher and Wiener 2017) and which can be the reason why previous vHIT studies, including older children, could not demonstrate significant age effects (Hamilton et al 2015;Janky et al 2015;Lehnen et al 2017;Retamal et al 2021;Ross and Helminski 2016). These major age effects in children below the age of 6 years may be related to maturational processes of the VOR cerebellar control (Wiener-Vacher and Wiener 2017).…”
Section: Normative Data and Age Effectsmentioning
confidence: 85%
See 1 more Smart Citation
“…More specifically, they found the most pronounced increase in VOR gain during early infancy until the age of 6 years old, after which a slower progression toward adultlike values was noted by the age of 16 years. The latter findings imply that progression in VOR gain mainly occurs early in life, which underlines the importance of age-appropriate normative data (Wiener-Vacher and Wiener 2017) and which can be the reason why previous vHIT studies, including older children, could not demonstrate significant age effects (Hamilton et al 2015;Janky et al 2015;Lehnen et al 2017;Retamal et al 2021;Ross and Helminski 2016). These major age effects in children below the age of 6 years may be related to maturational processes of the VOR cerebellar control (Wiener-Vacher and Wiener 2017).…”
Section: Normative Data and Age Effectsmentioning
confidence: 85%
“…Therefore, age-appropriate normative data are important to specify age trends across various response parameters of the pediatric vestibular test battery. Although several studies have previously published pediatric vestibular normative data and accompanying age trends, these studies mostly included older children, broad age categories, small sample sizes, and a limited number of vestibular tests, comprising large methodological differences (Kelsch et al 2006; Picciotti et al 2007; Valente 2007; Zagolski 2007; Casselbrant et al 2010; Maes et al 2014b; Hamilton et al 2015; Birdane et al 2016; Kastanioudakis et al 2016; Ross et al 2016; Lehnen et al 2017; Lotfi et al 2017; Siyamak et al 2017; Wiener-Vacher and Wiener 2017; Kuhn et al 2018; Bachmann et al 2018; Ahmad et al 2020; Retamal et al 2021). Even more important, pediatric vestibular normative data should be available when implementing vestibular screening in young patients to decide if referral for further assessment and intervention is needed, but without unnecessarily worrying parents.…”
Section: Introductionmentioning
confidence: 99%
“…They also found no age-related differences among adolescents, consistent with our data for adolescents aged 11–16 years old [ 39 ]. When using the EyeSeeCam device, Retamal et al found no differences between their 5–10-year-old and 11–17-year-old groups, although this research was also limited by a particularly small sample size [ 40 ]. Surprisingly, and contrasting with our findings, they also found differences between the VOR gain values of the right and left horizontal canals [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This remote setup allows the vHIT to be used from 3 months of age, while the other systems can be used from 3 years of age [41]. It is important to mention that the gain values are lowest under 3 years of age, after which there is a rapid increase up to the age of 6 years, with a subsequent slower increase in vHIT gain up to 16 years [41,42]. It is worth mentioning that in some studies, the gain in vHIT was found to be stable from 4 to 18 years [43].…”
Section: Vestibular Function Test In the Diagnosis Of Children Vertigomentioning
confidence: 99%